Correlation between Nutritional Status and Diarrhea in Toddlers at Slawi Health Center, Tegal, Central Java, Indonesia - Musdzalifah, Alfinatun; Khasanah, Uswatun; Zaidah, Niklah (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Diarrhea is a symptom of infection caused by bacteria, viruses, or parasites. It remains a significant public health issue in Indonesia that requires continued research and effective solutions. This study aimed to determine the relationship between nutritional status and the incidence of diarrhea among toddlers at the Slawi Public Health Center, Tegal Regency. Subjects and Method: A cross-sectional study was conducted in the working area of the Slawi Public Health Center from June to July 2023. A total of 190 subjects were selected for the study. The dependent variable was the incidence of diarrhea, while the independent variable was nutritional status. Nutritional status data were collected using height-for-weight measurements. Data were analyzed using the chi-square test. Results: Nutritional status was found to be associated with the incidence of diarrhea among toddlers. Toddlers with abnormal nutritional status had a 1.73 times higher risk of experiencing diarrhea compared to those with normal nutritional status, and this result was statistically significant (OR = 1.73; 95% CI = 1.13–2.66; p = 0.005). Conclusion: Abnormal nutritional status is associated with a higher incidence of diarrhea among toddlers.